Implementation of phase imbalance scheme for stabilizing torsional oscillations - Rachananjali Kunamneni; Suman S; Rambabu M; Ashok Kumar K (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This paper implements the phase imbalance scheme for damping torsional oscillations of a series capacitor compensated power system. The IEEE Second Benchmark Model, system-1, wherein two turbine generator model and two system model connected to an infinite bus is employed as a standard system model to study the concept of subsynchronous resonance. The turbine generator models have a common torsional mode. The Electromagnetic Transients Program (EMTP) is employed to simulate the damping effects provided by the phase imbalance scheme. The simulation results also show that parallel phase imbalance scheme gives the better damping characteristics when compared to that of series phase imbalance scheme.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6296